Schizophrenia in a Young Female with History of Childhood Sexual Abuse and Same Sex Relationship: A Case Report - Wulandari, Patricia; Rachmat Hidayat (Scientia Psychiatrica, 2023)
Introduction: Severe mental disorders in adulthood have various risk factors and causes. Childhood sexual abuse (CSA) is a risk factor that triggers developmental disorders and causes mental disorders in adulthood. This case report aims to present a patient with schizophrenia with a history of childhood sexual abuse and same-sex relationship. Case presentation: A young woman, a college student, came to the psychiatric unit of Cattleya Mental Health Center with her partner. Patients present with complaints of frequent self-harm and attempted suicide. The patient often feels voices telling her to scratch her hands and bang her head, saying that everyone in the world is trying to threaten her life. A mental state examination revealed that the patient's self-care was very poor and tended to be apathetic. Patients tend to be indifferent to the examiner, occasionally laughing and talking without direction (tangential). Her mood was elevated, affect was inappropriate. The patient experienced an auditory hallucination. Her risk factors include being born into a broken family, being an unwanted child, and was taken care of by a distant family (grandmother). As a child, the patient was raped by her uncle (a law enforcer) and was threatened if she told other family members. The patient was then treated with the oral antipsychotic olanzapine 5 mg daily and asked for a weekly follow-up. Patients are allowed to outpatient with supervision from her boarding friends and her girlfriend. Conclusion: Handling schizophrenia patients involves a multidisciplinary team starting from the introduction of risk factors to the selection of psychopharmacology and psychotherapy.